Ketahanan Pangan di Indonesia Tahun 2014-2021 - Fitria Eka Rahma; Arivina Ratih Yulihar; Ukhti Ciptawaty; I Wayan Suparta (CV. Multi Kreasi Media, 2023)
This study aims to analyze the effect of crop area, rice land productivity, and population on food security in Indonesia in 2014-2021. The method and analysis tool used in this study is panel data regression. The dependent variables used are food security and independent variables include crop area, land productivity, and population. The best model obtained is the Fixed Effect Model. The results showed that the area of harvested land and land productivity have a positive and significant effect on food security in Indonesia while the population has a negative and significant effect on food security in Indonesia.